Playing the Girl: The Possibilities of Forster’s Domestic Comedy - Emma Karin Brandin (Polish Journal of English Studies)
E. M. Forster once described what he had learnt from Jane Austen as “the possibilities of domestic humor” (Furbank & Haskell 2004, 14). His work has indeed often been labelled ‘domestic comedy’, ‘social comedy’ or ‘comedy of manners’, but few scholars have engaged seriously with the tactics and implications of his comedy. This paper suggests that one specific way in which Forster makes use of these possibilities is by exposing the constructed and performative nature of domestic femininity – and making fun of its absurdities. Forster’s domestic comedy is gentle in tone and outwardly in tune with the middle-class milieus that it portrays. In keeping with Eileen Gillooly’s concept of ‘feminine humour’, it undermines “the authority of [the cultural construction of femininity] even as it faithfully records the conditions, virtues, and behaviours required of life in the feminine position” (1999, 12). In A Room with a View and Howards End, the two novels that best represent his domestic comedy, Forster stages scenes and situations in which his female characters are expected to ‘play their part’ in order to uphold the rigid gender norms of Edwardian society. Lucy Honeychurch’s earnest effort to be ladylike involves studious mimicry as well as the occasional comic blunder, while Margaret Schlegel’s campaign as the submissive wife is shown to be both conscious and conflicted. Drawing on such illustrative examples, this paper demonstrates how Forster employs his distinct sense of humour to explore women’s attitudes and ambivalence towards this mandated performance of femininity, as well as to expose the hypocrisy of the society that demands it of them.